The role of transforming growth factor beta in tertiary dentinogenesis - Tetiana Haniastuti; Phides Nunez; Ariadna A. Djais (Dental Journal (Majalah Kedokteran Gigi), 2008)
The most visible repair response to pulp injury is the deposition of a tertiary dentin matrix over the dentinal tubules of the primary or secondary dentin. Tertiary dentin is distinguished as reactionary and reparative dentin, depending on the severity of the initiating response and the conditions under which the newly deposited dentin matrix was elaborated. Transforming growth factor beta (TGF-b) superfamily is a large group of growth factors that serve important roles in regulating cell growth, differentiation, and function. Members of this superfamily have been implicated in the repair process of the dental tissue after injury. Although numerous studies have proved that those bioactive molecules carry out an important role in the formation of tertiary dentin, comprehensive report regarding that phenomenon is not yet available. This review article aimed to summarize the role of TGF-b on tertiary dentinogenesis during the progression of a carious lesion.